Penerapan Sistem Informasi Keperawatan Virtually Nursing Technologies in Nursing Education: Sebuah Tinjauan Literatur - Deny Prasetyanto; Sukihananto Sukihananto (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Computer-based management information systems have begun to be widely used in the health environment especially in the field of nursing. A developing computer technology strategy for nursing education is the simultaneous use of virtual nursing. Management information systems in Indonesia are still experiencing many obstacles. Outside Indonesia, technology has a lot to help management of nursing education, especially the use of computers in nursing care. This computer is based on three dimensions, by working to simulate the experience of the patient as if it were real and in a risk-free environment, in which there are training sessions up to clinical decision making with diverse patient conditions, and immediately provide feedback. In Indonesia, the process of using computers in nursing documentation is very slow, so it needs to refresh the application of nursing information systems for the development of nursing education. Keywords: nursing documentation, virtual nursing management information system (VRS) ABSTRAK Sistem informasi manajemen berbasis komputer sudah mulai banyak digunakan di lingkungan kesehatan terutama dalam bidang keperawatan, Sebuah strategi teknologi komputer yang sedang berkembang untuk pendidikan keperawatan adalah penggunaan simultan virtual keperawatan. Sistem informasi manajemen di Indonesia ternyata masih banyak mengalami kendala. Di luar Indonesia, teknologi telah banyak membantu manajemen pendidikan keperwatan, terutama penggunaan komputer dalam asuhan keperawatan. Komputer ini berbasis tiga dimensi, dengan cara kerja mensimulasikan pengalaman pasien yang seakan nyata dan di lingkungan bebas risiko, di dalamnya terdapat sesi latihan sampai dengan pengambilan keputusan klinis dengan kondisi pasien yang beragam, serta langsung memberikan umpan balik. Di Indonesia, proses pemanfaatan komputer dalam dokumentasi keperawatan sangat lambat, sehingga perlu penyegaran penerapan sistem informasi keperawatan untuk pengembangan pendidikan keperawatan. Kata kunci: dokumentasi keperawatan, sistem informasi manajemen keperawatan, simultan virtual (VRS)